Nilai Kerja Lansia Abdi Dalem Keraton Yogyakarta Pasca UU Keistimewaan Yogyakarta - Nurus Sa'adah (LP2M UIN Sunan Kalijaga, 2017)
Statistical data shows that Yogyakarta Special Region (Daerah Istimewa Yogyakarta – DIY) has the largest number of elderly in comparison to other provinces throughout Indonesia. As a province headed by a sultan, there is a tendency for residents of Yogyakarta to serve as courtiers to the Yogyakarta Sultanate for life. More than 50% of the 2200 courtiers are over 60 years old (elderlies). These elderly courtiers willingly serve for decades without pay as they only expect to be afforded “peparingan” (charity contributions) from the Sultan. With the implementation of the Law on Privileges of Yogyakarta as a Special Region year 2012, the wages for courtiers have since multiplied compared to the Sultan’s previous peparingan. The object of this research is to find a tendency in the work value of elderly courtiers in the Yogyakarta Sultanate and examine whether changes in work value before and after the issuance of the Law on Privileges of Yogyakarta occurred. Data collection was conducted through interviews with 12 punokawan courtiers working in the Yogyakarta Sultanate. Results show that elderly courtiers tend to possess work value relating to comfort, altruism, and status. No difference in these three work values were observed before and after the implementation of the Privileged Fund that lead to additional income, this is because added income is considered as a blessing for their continuous whole-hearted services.